Histological and immunohistochemical study of the expression of p53 and ki-67 proteins in the mucosa of the tongue, pharynx and larynx of rats exposed to cigarette smoke - Semenzati, Graziela de Oliveira [UNESP]; Salgado, Breno de Souza [UNESP]; Rocha, Noeme Sousa [UNESP]; Matheus, Selma Maria Michelin [UNESP]; de Carvalho, Lidia Raquel [UNESP]; Garcia Martins, Regina Helena [UNESP] (Informa Healthcare, 2012)
Introduction: Head and neck cancers are linked to smoking. The most affected sites are the oral cavity, pharynx and larynx. Experimental studies show epithelial lesions caused by cigarette smoke. Objectives: To investigate in rats the effects of acute cigarette smoke exposure on the mucosa of the tongue, pharynx and larynx.Material and method: Wistar rats were allocated into two groups of 20 animals: CG (control) receiving food and water ad libitum and TG (Tobacco) exposed to the smoke of 40 cigarettes/day for 60 days. Biopsy of their tongues, pharynxes and larynxes were subjected to histopathological, histomorphometric and immunohistochemical studies of protein p53 and ki-67.Result: The histological analysis of tongue from the Tobacco group revealed epithelial hyperplasia (90%), basal cell hyperplasia (95%) and mild to moderate dysplasia (85%). In pharynx showed basal cell hyperplasia (85%), dysplasia (25%) and vascular congestion (95%). In larynx showed basal cell hyperplasia (70%), epithelial hyperplasia (55%), congestion (100%) and inflammatory infiltrate (25%). Morphometric analysis revealed that keratin layer thickness was greater in the tobacco group. P53 immunoexpression was negative in both groups. Ki-67 immunoexpression was positive in basal cell nuclei but in parabasal cell nuclei it was positive only in the Tobacco group.Conclusions: The exposure of animals to cigarette smoke for 60 days resulted in benign lesions. The duration of exposure was not enough to cause the development cancer, as confirmed by the negative expression of p53 protein in all slides examined. Analysis of ki-67 expression showed intense epithelial proliferation in response to damage.
Keywords: Airways; experimental study; histopathological; ki-67; p53; rats; tobacco